8 - ‘Embedded Practices’: A Review of Political Corruption in Africa: Extraction and Power Preservation Inge Amundsen (Ed.) Cheltenham: Edward Edgar Publishing ISBN 978 1 78897 251 2 (cased); ISBN 978 178897 252 9 (eBook), (2019) pp +201 - Oloyede, Olajide (African Sociological Review, 2022)
Abstract